Social peers rescue autism-relevant sociability deficits in adolescent mice - Yang, Mu; Perry, Kayla; Weber, Michael D; Katz, Adam M; Crawley, Jacqueline N (Autism research, 2011)
Behavioral therapies are currently the most effective interventions for treating the diagnostic symptoms of autism. We employed a mouse model of autism to evaluate components of behavioral interventions that improve sociability in mice. BTBR T+tf/J (BTBR) is an inbred mouse strain that exhibits prominent behavioral phenotypes with face validity to all three diagnostic symptom categories of autism, including robust and well-replicated deficits in social approach and reciprocal social interactions. To investigate the role of peer interactions in the development of sociability, BTBR juvenile mice were reared in the same home cage with juvenile mice of a highly social inbred strain, C57BL/6J (B6). Subject mice were tested as young adults for sociability and repetitive behaviors. B6 controls reared with B6 showed their strain-typical high sociability. BTBR controls reared with BTBR showed their strain-typical lack of sociability. In contrast, BTBR reared with B6 as juveniles showed significant sociability as young adults. A 20-day intervention was as effective as a 40-day intervention for improving social approach behavior. High levels of repetitive self-grooming in BTBR were not rescued by peer-rearing with B6, indicating specificity of the intervention to the social domain. These results from a robust mouse model of autism support the interpretation that social enrichment with juvenile peers is a beneficial intervention for improving adult outcome in the social domain. This novel paradigm may prove useful for discovering factors that are essential for effective behavioral treatments, and biological mechanisms underlying effective behavioral interventions.